Effectiveness of TikTok Social Media Advertising as an Online Promotion Strategy for CV Avero Indonesia - Adzra, Rifda Shabrina; Iryanti, Endang (PT FORMOSA CENDEKIA GLOBAL, 2024)
Advertising is one way to market products in the digital era by utilizing social media as a marketing tool to expand its market reach without limits. Implementing the right online promotional strategy is very necessary to attract consumer attraction through TikTok social media. This research aims to analyze the effectiveness of TikTok social media advertising as an online promotion strategy for CV Avero Indonesia and analyze the content characteristics of TikTok @averoofficial advertising as an online promotion strategy for CV Avero Indonesia. This research is qualitative research using the library research method. The research results can conclude that advertising via TikTok social media is quite effective as an online promotion strategy for CV Avero Indonesia. The advertising promotion strategy delivered by the TikTok account @averoofficial is in line with the AIDA stages, which attract a lot of attention and increase the audience seen from the number of followers of the TikTok account.